PELATIHAN PEMBUATAN KORESPONDENSI DENGAN PEMANFAATAN MAIL MERGE PADA MICROSOFT WORD BAGI SEKRETARIS OSIS SMA DI KABUPATEN PEKALONGAN - Aria Mulyapradana; Aria Elshifa; Ary Dwi Anjarini (Jurnal Pengabdian Masyarakat Kesosi, 2022)
The creation of correspondence needs to pay attention to the rules in writing official letters. To minimize errors in writing in letters such as the use of ineffective sentences, errors in writing people's names and positions, it is necessary to compile sentences, good and correct word selection and spelling. Correspondence made by the Student Council Secretary uses Microsoft word so it takes a long time if you have to make a large number of letters to be delivered to all members of the student council. In order to facilitate these activities, training was carried out on how to make letters in large quantities easily, quickly, effectively and efficiently. The purpose of this community service activity was that as many as 25 participants from representatives of the High School Student Council Secretary in Pekalongan Regency gained knowledge about correspondence and the use of mail merge on Microsoft word to support activities in their organization. This activity starts from the preparation, implementation and evaluation of activities. The result of the activity was that the participants were enthusiastic and responsive in participating in the activity, with the hope that the student council administrators could be more skilled in making letters in large quantities and minimize the occurrence of errors in writing letters.